Momentum Distribution Studies of Projectile Fragments from Peripheral Collisions Below the Fermi Energy - Fasoula, Olga; Souliotis, George A.; Koulouris, Stergios; Palli, Konstantina; Veselsky, Martin; Jenello, Sherry J.; Bonasera, Aldo (HNPS Advances in Nuclear Physics, 2023)
This paper presents our recent studies of multinucleon transfer in peripheral collisions in reactions below the Fermi regime. Our current focus is the study of the mass, angular and momentum distributions of the projectile-like fragments from the reaction of an 86Kr beam at 15 MeV/nucleon with a target of 64Ni. Experimental data from our previous work with the MARS spectrometer at the Cyclotron Institute of Texas A&M University were compared with model calculations. The dynamical stage of the reaction is described with either the Deep-Inelastic Transfer Model (DIT) or with the microscopic Constrained Molecular Dynamics model (CoMD). The de-excitation of the hot projectile-like fragments is performed with the GEMINI model. The momentum distributions are characterized by a quasi-elastic peak and a deep-inelastic peak. Two-body kinematics was employed to extract the total excitation energies of these regions. Through the thorough study of peripheral reactions in the Fermi energy regime we expect to gain valuable information that could lead to the understanding of how the rare isotopes in regions such as the r-process path and the neutron drip line are formed and the reaction mechanism(s) that take place.